Optofluidic chip for living cell detection and culture - Yu, Jiaqing (2014)
In this PhD thesis, a droplet optofluidic diffraction grating is designed based on multiphase microdroplet technology; a droplet optofluidic system is developed to detect bacteriophages in water sample via host cell growth in microdroplet carrier and endothelial cell is cultured and its dysfunction under different physical and chemical conditions is measured using a hemodynamic microfluidic chip. The reconfigurable optical diffraction grating using multiphase optofluidic droplets is designed based on a microdroplet system. The formation process of droplets in microfluidic T-junction geometries is described. The optical droplet grating works with high stability and tunability in grating period. Refractive index variation and various diffraction patterns are obtained. The grating is developed as a phase-transmission-grating-based compact optofluidic refractometer and zero-order transmission color filters, making it promising for biochemical and bio-material applications. The droplet-based optofluidic system to detect bacteriophages is designed and fabricated. The sample containing bacteriophages is mixed with the host cell, Escherichia coli, and divided into a large amount of microdroplets. The growth of the host cell is monitored by the scattering pattern of the microdroplet carrier and the pattern is analyzed by using the mean power frequency. A real-time, label-free and high sensitivity quantification of bacteriophage is achieved and low concentration bacteriophage in water sample can be detected with high accuracy and stability. Finally, a hemodynamic lab-on-a-chip microsystem is developed and used to study how hyperglycemia leads to the dysfunction of the endothelial cell. The endothelial cells are cultured in microfluidic chips under different physical and chemical conditions, which can mimic the physiological pulsatile flow profile of blood vessel. The intracellular reactive oxygen species (ROS) level is determined using real-time fluorescence microscopy and the cell apoptosis is detected based on a caspase-3 based fluorescence resonance energy transfer (FRET) biosensor cell line which can detect endothelial cell apoptosis in real-time, post-treatment effect with limited cell sample. The successful developments of living cell culture and detection are achieved using the microfluidic chip. The droplet grating shows a refractive index unit (RIU) detection limit of 6.3 × 10-5 when used as an optofluidic refractometer. It also can produces different colors when used as a color filter. The water sample with the bacteriophage concentration lower than 102 pfu/ml is detected